Application of Provisions on Restorative Justice in Criminal Acts of Domestic Violence: A Study of Decision Number 56/PID.SUS/2020/PN BDW - Kwekdinata, Winson; Fernando, Fernando; Adawiyah, Rodiatun (International Journal of Business, Law, and Education, 2025)
The resolution of criminal acts through restorative justice, as demonstrated in Decision Number 56/Pid.Sus/2020/PN BDW, provides an alternative mechanism for handling criminal cases, including complaint-based offenses. Although reconciliation was achieved between the defendant and the victim-witness, the defendant was nevertheless found guilty and sentenced to three months of imprisonment. The central issue examined in this study is whether the application of restorative justice in domestic violence cases aligns with Law Number 23 of 2004 and whether the judicial decision is consistent with prevailing legal standards. This research employs a normative and descriptive-analytical approach based on secondary data. The findings indicate that the application of restorative justice in this case adheres to the procedures outlined in the Decree of the Director General of the General Courts No. 1691/DJU/SK/PS.00/12/2020. Despite reconciliation and the withdrawal of the complaint, such actions do not eliminate the defendant’s criminal liability. Although the court ruled that the defendant was not required to serve the prison sentence, the researchers argue that reconciliation achieved through restorative justice should not merely serve as a mitigating factor but should instead form the legal basis for exemption from punishment. Moreover, the regulatory framework for resolving domestic violence cases through restorative justice should be developed in greater detail. When a domestic violence case fails to meet the formal requirements for restorative justice, the conventional criminal justice process should apply.